Skrb za otroke - Kuhar, Metka (Teorija in praksa, 2011)
The article analyses the significance of different types of parenting social support in late modernity and outlines the situation in Slovenia - i.e. the relative closedness of Slovenian families within narrow kin relationships. On the basis of the study "Needs of preadolescent children's parents in Slovenia"and other research findings, the article presents the formal and non-formal support resources of preadolescent children's parents, their satisfaction with these forms of support, their parenting needs, their relationship to the potential use of the family centre institution and the factors influencing their viewpoint. On the basis of the findings the final part sets out the parental need for family centres in Slovenia
Keywords: child; Children; Otroci; Adolescenca; Adolescence; Parents; Starši; Needs; Potrebe; družinski centri; materinski centri